PWE-160 Exploring Gastrointestinal Symptoms and Their Impact on Quality Of Life in Patients With Neuroendocrine Tumours. (17th August 2016) - Williams, M; Reid, K; Lewis, J; Christian, A; Sunderraj, L; Williams, H; Rees, A; Khan, MS
Abstract : Introduction: Treatments available to patients with neuroendocrine tumours(NETs) have been studied for their effect on tumour progression and carcinoid syndrome. However, there is minimal evidence on gastrointestinal (GI) symptom burden and its impact on quality of life (QoL). We aimed to determine whether patients with NETs receiving treatment experience GI symptoms, and to explore the impact that these symptoms have on QoL. Methods: A prospective cohort of 46 patients with histologically confirmed NET visiting endocrine and oncology clinics completed GSRS (gastrointestinal symptom rating scale) and EORTC QLQ-GINET21 QoL questionnaires prior to establishment of a gastroenterology NET service. Results: The majority of patients had a midgut(70%) or pancreatic(15%) primary with 96% having metastatic disease. Duration of diagnosis was 42 months (range 2–249), 91% having stable disease. The majority of patients reported GI symptoms including: abdominal cramps(80%), bloating(74%), excessive passing of wind(87%) and faecal urgency(87%). 50% had a stool frequency of more than 5 times a day and 71% of patients scored type 5 or higher on the Bristol Stool Chart. 54% of patients reported greasy/oily stool. 60% scored their QoL to be less than 7 out of 10. When asked how much bowel symptoms were affecting quality of life, 58% of patients scored more than 5 out of 10. 97% reported their illness to be distressing for those close to them. Conclusion: This study represents the first systematic analysis of specifically defined GI symptoms experienced by NET patients. Despite having stable disease, many patients frequently experience GI symptoms which have a negative impact on QoL. Disclosure of Interest: None Declared